2020
DOI: 10.1111/pce.13693
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in source and sink traits affects the response of photosynthesis and growth to elevated atmospheric CO2

Abstract: This study aimed to understand the response of photosynthesis and growth to e‐CO2 conditions (800 vs. 400 μmol mol−1) of rice genotypes differing in source–sink relationships. A proxy trait called local C source–sink ratio was defined as the ratio of flag leaf area to the number of spikelets on the corresponding panicle, and five genotypes differing in this ratio were grown in a controlled greenhouse. Differential CO2 resources were applied either during the 2 weeks following heading (EXP1) or during the whole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 114 publications
(199 reference statements)
4
39
1
Order By: Relevance
“…Several studies showed similar results-e.g., a synchronous increase in Pn, C i , and WUE was observed in the Paris polyphylla cultivars under eCO 2 concentrations (800 µmol mol − 1 ), while g s and Tr remained unchanged [30]. Consistently, different Indica rice cultivars showed an increase in Pn under eCO 2 but no signi cant variations in leaf chlorophyll content during short-term eCO 2 treatment [31].…”
Section: Physiological Response To Ecosupporting
confidence: 54%
“…Several studies showed similar results-e.g., a synchronous increase in Pn, C i , and WUE was observed in the Paris polyphylla cultivars under eCO 2 concentrations (800 µmol mol − 1 ), while g s and Tr remained unchanged [30]. Consistently, different Indica rice cultivars showed an increase in Pn under eCO 2 but no signi cant variations in leaf chlorophyll content during short-term eCO 2 treatment [31].…”
Section: Physiological Response To Ecosupporting
confidence: 54%
“…The mitigation of the photosynthesis level for the SR treatment under eCO 2 was due to the increase in NSC in the leaves (Supplementary Figure 5 and Supplementary Table 1). Fabre et al (2020) also pointed out that low sourcesink ratio cultivars had greater gains in photosynthesis because they accumulated less NSCs in the flag leaf than high sourcesink ratio cultivars. Conversely, leaf-cutting treatments (LCs) enhanced the Pn response of the remaining leaves to eCO 2 (i.e., LC1 enhanced Pn of the second leaf and LC3 enhanced Pn of the fourth leaf).…”
Section: Source-sink Relationships Affect Sugar Accumulation and Photosynthesis Under Ecomentioning
confidence: 98%
“…As we cannot really decide on the role of sugars in the present study, more research is needed on the regulation of carbohydrate accumulation and remobilization in the context of source-sink relationships. Fabre et al (2020), using five naturally contrasting cultivars in terms of their source-sink ratio to investigate the response of photosynthetic capacity to eCO 2 , found a negative correlation between source-sink ratio and the response of Pn. Therefore, compared with a high source-sink ratio, a low source-sink ratio may be more conducive to improve photosynthetic capacity and maximize the 'fertilizer effect' of eCO 2 .…”
Section: Source-sink Relationships Affect Sugar Accumulation and Photosynthesis Under Ecomentioning
confidence: 99%
See 2 more Smart Citations